Buserelin shortens the estrus-to-ovulation interval and improves the pregnancy outcomes in gilts treated with a fixed-time artificial insemination - Shi, Zhicheng; Wang, Zongyu; An, Lei; Li, Zhi; Cheng, Linghua; Yue, Yuan; Guo, Min; Wang, Xiaodong; Liu, Haiqing; Ren, Li; Tian, Jianhui; Li, Qin; et al. (Frontiers in Veterinary Science, 2025)
Fixed-time artificial insemination (FTAI) is currently a standardized protocol for pig reproductive management. Efficient ovulation synchronization induced by GnRH analogs is critical for ensuring the pregnancy outcomes of FTAI. However, among the widely used GnRH analogs, the degree of synchronization and timing of ovulation remain unclear in gilts. In the present study, we focused on the estrus-to-ovulation interval, a key component in fertility management programs, and directly compared the follicular dynamics and timing of ovulation, and the subsequent pregnancy outcomes between two well-established GnRH analogs buserelin and gonadorelin. 224 prepubertal Large White gilts, randomly divided into three independent batches, were allotted to this study. The administration of PMSG was aligned with the FTAI protocol, with gonadorelin or buserelin injections administered upon detection of estrus onset in gilts. Ovarian ultrasonography was performed at the onset of estrus. Serum samples were collected for LH detection. Total piglets born, born alive, and other performance indicators were measured. Our results showed that buserelin-treated gilts exhibited an earlier ovulation, as well as a shorter estrus-to-ovulation interval and a centralized ovulation duration, with 81.5% ovulation occurring within 24–48 h after buserelin injection. Additionally, although the pregnancy rate and farrowing rate didn't differ between the two analogs, buserelin administration is beneficial for the number of total piglets and the piglet index. In conclusion, our data demonstrate that buserelin has advantages in centralizing induced ovulation and thus improving FTAI outcomes.